THE OLD TEA PLANTS (CAMELLIA SINENSIS (L.) KUNTZE) : POTENTIAL AS NATURAL SOURCE ANTIOXIDANT - Susana, Valerina
Free radicals are reactive molecules that can cause negative effects on the body such as premature aging and cancer, among other things. Natural antioxidants in plants can play a role in neutralizing free radicals. Tea (Camellia sinensis (L.) Kuntze) is a natural antioxidant. This research aims to determine the antioxidant activity of leaves, roots and twigs of old tea extracts using the DPPH and CUPRAC methods, determine total phenols and flavonoids, the correlation of total phenols and flavonoids with antioxidant activity, correlation between the two methods, as well as identification and determination of compound levels of flavonoids in selected extracts. Antioxidant activity was determined using the DPPH and CUPRAC methods and total phenol and flavonoid levels were determined using UV-visible light spectrophotometry. The Identification and determination of flavonoid compounds were made using high-performance liquid chromatography. The antioxidant activity of tea leaves, roots and twig extracts using the DPPH method had a value in a range of 8.945 – 405.758 mg AEAC/g, while the antioxidant activity using the CUPRAC method 18.197 – 244. 713 mg AEAC/g. The highest total phenol content was provided by the ethanol extract of tea leaves, amounting to 171.910 ± 1.876 mg GAE/g. The highest total flavonoid content was provided by ethyl acetate extract of tea leaves, amounting to 49.694 ± 1.031 mg QE/g. The extract’s total phenol and flavonoid levels correlate strongly to very strongly with the antioxidant activity values using the DPPH and CUPRAC methods. Phenolic and flavonoid compounds greatly contributed to the antioxidant activity in old tea leaves, roots and twig extracts using the DPPH and CUPRAC methods. The antioxidant activity values of the extracts from both methods gave linear results with a strong to very strong correlation. Rutin, quercetin, and apigenin were found in ethanol leaves extract of old tea with 9.90 ± 0.14 mg/g; 0.88 ± 0.21 mg/g; and 0.39 ± 0.02 mg/g. respectively. The leaves, roots and twigs of old tea have the potential to be developed as natural antioxidant agents